Grammatical Errors of the Writing Skills found in English Descriptive Texts by the Students of Junior High School Number 3 Sukawati (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2025)
This study entitled “Grammatical Errors in the Writing Skills of English Descriptive Texts by Students of Junior High School Number 3 Sukawati”, to aims and analyzed the types of errors that made by students in writing English descriptive texts and the factors that can cause the errors. The data were collected from the assignment of writing English descriptive text from 40 students in grade VIIB and taken from the two questionaries that enveloped the question about the factor that might cause an error happened. The first data were collected from the assignment of writing English descriptive texts by checking one by one the data to found the error type in writing following by  the theory that purposed by Keshavarz (2011) in his book entitled “Contrastive Analysis and Error Analysis” which divided the error types into four types and for the questionaries that has prepare are following by the theory that  has purposed by Richard (1974) in his book entitled “Error Analysis in English Perspective on Secon Language Acquisition” which divided the factor that might caused error into seven types. This study was used the mix approached of the qualitative and quantitative method to obtain the comprehensive understanding. The total data of error that were found from the English descriptive text that has been write by the student was 80 errors, those are omission with the total of 43 errors or 53,75%, addition with 6 errors (7,5%), substitution was 27 errors or 33,75% and the permutation found with the total of 5% or 4 errors. From the linguistic session, there were found 31 errors in morphology or (51.67%) and 29 errors or 48,33% come from syntax. Furthermore, the factors that caused the errors were occurs due to the interference from influence of the first language that owned by the student, language interference, sociolinguistic situations, modality, and age. Thus, it can be concluded that language transfer from the mother tongue to the second language greatly affects students' writing skills, this is also in line with social conditions, student age, and modality of the students.